2020
DOI: 10.3390/pharmacy8010024
|View full text |Cite
|
Sign up to set email alerts
|

Prescriber-Initiated Engagement of Pharmacists for Information and Intervention in Programs of All-Inclusive Care for the Elderly

Abstract: Little is known about the types of drug information inquiries (DIIs) prescribers caring for older adults ask pharmacists during routine practice. The objective of this research was to analyze the types of DIIs prescribing clinicians of Programs of All-Inclusive Care for the Elderly (PACE) made to clinical pharmacists during routine patient care. This was a retrospective analysis of documented pharmacists’ encounters with PACE prescribers between March through December, 2018. DIIs were classified using a develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Underscoring these challenges, a recent study found that PACE physicians and nurse practitioners frequently initiated consultation with pharmacists for information and advice when faced with medication safety uncertainties [16]. Notably, their inquiries commonly pertained to opioids and psychoactive drugs [16], which are medication classes responsible for the disproportionate amount of ADE claims identified in the present study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Underscoring these challenges, a recent study found that PACE physicians and nurse practitioners frequently initiated consultation with pharmacists for information and advice when faced with medication safety uncertainties [16]. Notably, their inquiries commonly pertained to opioids and psychoactive drugs [16], which are medication classes responsible for the disproportionate amount of ADE claims identified in the present study.…”
Section: Discussionmentioning
confidence: 71%
“…The CDSS helps pharmacists identify and resolve specific medication-related problems [12] as well as optimize medication regimens based on available pharmacogenomic information [15]. Prescribers and pharmacists commonly collaborate to improve medication safety and reduce ADE risk [12,16].…”
Section: Study Design Setting and Contextmentioning
confidence: 99%
“…While this is likely the biggest contributor to the reduction in costs here than what was reported by Stein et al, other ancillary components of MRM that are unavailable in the EMTM setting could also help explain this difference. For example, adherence support services, pharmacogenomic consultations, and prescriber-initiated engagement of PACE pharmacists for drug information are all expected to optimize regimens and improve outcomes [ 13 , 44 , 45 ]. Future research must evaluate which MRM components are most impactful to economic and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical pharmacists provide expert advice to prescribers needing drug information prior to making a clinical decision [ 13 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation